Preparation and application of chitosan modified ferroferric oxide

By combining chitosan with iron tetraoxide to prepare a modified adsorbent, the problem of removing alizarin green in water was solved, and efficient adsorption and environmentally friendly decontamination effects were achieved.

CN119455905APending Publication Date: 2025-02-18JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411590772.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove alizarin green dye from water, and traditional methods are prone to secondary contamination.

Method used

By combining chitosan with iron tetraoxide, chitosan modified iron tetraoxide was prepared as an adsorbent, and it utilized its electrical neutralization ability and magnetic properties under acid-base conditions to efficiently adsorb alizarin green in water .

Benefits of technology

It achieves efficient adsorption of alizarin green in water, with an adsorption rate of more than 50%, and avoids secondary pollution, with good biocompatibility and low toxicity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455905A_ABST
    Figure CN119455905A_ABST
Patent Text Reader

Abstract

The invention discloses preparation and application of chitosan modified ferroferric oxide. Comprising the following steps: mixing an alcohol solvent with ferric trichloride, adding chitosan, and uniformly stirring to obtain a first reaction solution; adding an alcoholic solution of sodium acetate into the first reaction solution, violently stirring, and heating to react to obtain a first product; and cooling the first product, separating by using a magnet to obtain a black substance, and washing and drying the black substance to obtain the chitosan modified ferroferric oxide. The chitosan modified ferroferric oxide prepared by the method can be applied to water to adsorb alizarin green, and the specific steps comprise: mixing the chitosan modified ferroferric oxide with an alizarin green aqueous solution, carrying out oscillation adsorption, and carrying out magnetic separation on the chitosan modified ferroferric oxide after adsorption. The specific adsorption rate of the prepared CS-coated Fe3O4 to alizarin green can reach 50% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the preparation and application of a water-soluble dye adsorption material, and in particular to the preparation of chitosan-modified ferrosoferric oxide and the application of the chitosan-modified ferrosoferric oxide in the adsorption of alizarin green. Background Art

[0002] The dye production industry and many other industries using dyes and pigments generate wastewaters that are high in color and organic content. Discharge of highly colored dye wastes can disrupt biological processes in streams by hindering the penetration of light. In addition, many dyes are toxic to certain organisms and these toxic and hazardous substances are responsible for many serious problems of infection in humans, animals and plants and may also directly damage aquatic biota. Therefore, the removal of dyes from these wastewaters is a major environmental concern.

[0003] At present, there are many methods to remove dyes from water, such as biodegradation, electrochemical treatment spectrum, photocatalysis, etc. However, improper methods are prone to secondary pollution. Adsorption has the advantages of being simple, fast, and green. The large number of amino, hydroxyl, and acetyl groups in chitosan molecules form a cage-like molecular structure. Under certain acid-base conditions, chitosan can chelate heavy metal ions and adsorb them. The free -NH2 in chitosan can react with H + The combination makes chitosan positively charged, thereby neutralizing the negatively charged organic matter and purifying the water. At the same time, ferroferric oxide has superparamagnetism, and subsequent recycling and treatment are also very convenient, thus avoiding secondary pollution of water quality. Summary of the invention

[0004] Purpose of the invention: The purpose of the present invention is to provide a method for preparing chitosan-modified ferroferric oxide, so as to solve the problem of how to prepare chitosan-modified ferroferric oxide. Another purpose of the present invention is to propose an application of chitosan-modified ferroferric oxide in adsorbing alizarin green in water, so as to solve the problem of how to adsorb and remove alizarin green in water.

[0005] Technical solution: The method for preparing chitosan-modified ferroferric oxide of the present invention comprises the following steps:

[0006] (1) mixing an alcohol solvent and ferric chloride, adding chitosan, and stirring to obtain a first reaction solution;

[0007] (2) adding an alcohol solution of sodium acetate to the first reaction solution, stirring vigorously and then heating to react to obtain a first product;

[0008] (3) Cooling the first product and separating it with a magnet to obtain a black substance, washing and drying the black substance to obtain chitosan-modified ferrosoferric oxide.

[0009] Preferably, in step (1), the alcohol solvent comprises at least one of ethylene glycol, propylene glycol, butylene glycol and pentanediol, and the ferric chloride is FeCl3·6H2O.

[0010] Preferably, in step (1), the solid-liquid ratio of chitosan, ferric chloride and alcohol solvent is 0.5-1.5 g: 2-5 g: 60-100 mL.

[0011] Preferably, in step (2), the alcohol solution of sodium acetate is prepared by dissolving 10-14 g of sodium acetate in 15-25 mL of ethylene glycol, and the volume ratio of the alcohol solution of sodium acetate to the alcohol solvent is 1:3-5.

[0012] Preferably, in step (2), the vigorous stirring time is at least 20 minutes, and the heating reaction conditions are 170-200° C. and the reaction time is 10-14 hours.

[0013] Preferably, in step (3), the washing method is washing with ultrapure water and anhydrous ethanol.

[0014] Another aspect of the present invention discloses application of chitosan-modified ferrosoferric oxide prepared by the preparation method in adsorbing alizarin green in water.

[0015] The present invention uses chitosan to modify ferroferric oxide, and uses the modified material as an adsorbent for the adsorption study of alizarin green. The present invention aims to comprehensively evaluate the influence of various factors on the adsorption effect, including the quality of the adsorbent, the concentration of the solution, the adsorption time, the adsorption temperature and the pH value of the solution. Under the optimal adsorption conditions, the chitosan-modified ferroferric oxide prepared by the present invention can efficiently adsorb alizarin green in water.

[0016] The specific steps of the application include mixing chitosan-modified ferroferric oxide with an alizarin green aqueous solution, then oscillating and adsorbing the mixture, and magnetically separating the chitosan-modified ferroferric oxide after adsorption.

[0017] Preferably, the concentration of the alizarin green aqueous solution is 10-80 μg / mL, and the pH value is 2-11; the solid-liquid ratio of the chitosan-modified ferrosoferric oxide to the alizarin green aqueous solution is 10-30 mg: 1-30 mL.

[0018] Preferably, the oscillating adsorption condition is mechanical oscillating adsorption at 25-45°C for 20-180 min.

[0019] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages:

[0020] Based on the good biocompatibility and low toxicity of CS@Fe3O4, the present invention has developed a rapid and simple method for adsorbing dyes in wastewater, thereby achieving the removal of dyes in environmental samples. The specific adsorption rate of CS@Fe3O4 prepared by the present invention for alizarin green can reach more than 50%. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a characterization result diagram of chitosan-modified ferrosoferric oxide prepared in Example 1. DETAILED DESCRIPTION

[0022] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.

[0023] Example 1: A method for preparing chitosan-modified ferrosoferric oxide is as follows:

[0024] Add 3.6g FeCl3·6H2O to 80mL ethylene glycol, stir for 30min, and then add 1g chitosan (CS) to the solution. Subsequently, add 20mL ethylene glycol solution containing 12g sodium acetate to the above solution, stir vigorously for 30min, and then put it into an autoclave, set the temperature to 185℃, and react for 12h. After the reaction, cool the solution to room temperature, separate the black sample with a magnet, wash it three times with ultrapure water and anhydrous ethanol, and place the solid sample in an oven at 60℃ to dry for 6h for later use. The test results of chitosan-modified ferroferric oxide are as follows: Figure 1 shown.

[0025] The prepared chitosan-modified ferroferric oxide was used to adsorb alizarin green in water as follows:

[0026] Chitosan-modified ferroferric oxide was mixed with an alizarin green aqueous solution with an initial concentration of 40 μg / mL and a pH value of 2 at a material-liquid ratio of 20 mg:20 mL, and mechanically oscillated for adsorption at 25°C for 120 min. After adsorption, the chitosan-modified ferroferric oxide was magnetically separated by a magnet, and the concentration of alizarin green in the remaining aqueous solution was determined. The adsorption rate was calculated according to the following formula:

[0027] Adsorption rate (%) = (initial Alizarin Green concentration - Alizarin Green concentration of aqueous solution after adsorption treatment) / initial Alizarin Green concentration × 100%.

[0028] Example 2: A method for preparing chitosan-modified ferrosoferric oxide is as follows:

[0029] Add 2g FeCl3·6H2O to 60mL ethylene glycol, stir for 30min, and then add 0.5g chitosan (CS) to the solution. Subsequently, add 20mL ethylene glycol solution containing 10g sodium acetate to the above solution, stir vigorously for 30min, and then put it into an autoclave, set the temperature to 170℃, and react for 14h. After the reaction, cool the solution to room temperature, separate the black sample with a magnet, wash it three times with ultrapure water and anhydrous ethanol, and place the solid sample in an oven at 60℃ to dry for 6h for later use.

[0030] The prepared chitosan-modified ferroferric oxide was used to adsorb alizarin green in water as follows:

[0031] Chitosan-modified ferroferric oxide was mixed with an alizarin green aqueous solution with an initial concentration of 10 μg / mL and a pH value of 7 at a material-liquid ratio of 10 mg:30 mL, and mechanically oscillated for adsorption at 45°C for 40 minutes. After adsorption, a magnet was used to magnetically separate the chitosan-modified ferroferric oxide.

[0032] Example 3: A method for preparing chitosan-modified ferrosoferric oxide is as follows:

[0033] Add 5g FeCl3·6H2O to 100mL ethylene glycol, stir for 30min, and then add 1g chitosan (CS) to the solution. Subsequently, add 25mL ethylene glycol solution containing 14g sodium acetate to the above solution, stir vigorously for 30min, and then put it into an autoclave, set the temperature to 200℃, and react for 10h. After the reaction, cool the solution to room temperature, separate the black sample with a magnet, wash it three times with ultrapure water and anhydrous ethanol, and place the solid sample in an oven at 60℃ to dry for 6h for use.

[0034] The prepared chitosan-modified ferroferric oxide was used to adsorb alizarin green in water as follows:

[0035] Chitosan-modified ferroferric oxide was mixed with an alizarin green aqueous solution with an initial concentration of 80 μg / mL and a pH value of 8 at a material-liquid ratio of 30 mg:1 mL, and mechanically oscillated for adsorption at 35°C for 180 min. After adsorption, the chitosan-modified ferroferric oxide was magnetically separated using a magnet.

[0036] Example 4: Taking the solid-liquid ratio of chitosan-modified ferroferric oxide to alizarin green aqueous solution as a variable, the amount of chitosan-modified ferroferric oxide used as an adsorbent was screened and optimized as follows:

[0037] The rest is the same as Example 1, except that: the material-liquid ratio gradient is set to 5, 10, 15, 20, 25 mg: 20 mL; adsorption treatment is performed respectively, and the results are shown in Table 1:

[0038] Table 1 Effect of different material-liquid ratios on adsorption rate

[0039]

[0040]

[0041] As can be seen from Table 1, when the solid-liquid ratio is 1 mg / mL, the adsorption rate is high and further increasing the amount of chitosan-modified ferroferric oxide does not significantly improve the adsorption rate, so the solid-liquid ratio is selected to be 1 mg / mL.

[0042] Example 5: Using the initial concentration of the alizarin green aqueous solution as a variable, the concentration of the alizarin green aqueous solution suitable for adsorbent work was screened and optimized as follows:

[0043] The rest is the same as Example 1, except that the initial concentration gradient of the alizarin green aqueous solution is set to 10, 20, 30, 40, 60, 80 μg / mL; adsorption treatment is performed respectively, and the results are shown in Table 2:

[0044] Table 2 Effect of initial concentration of alizarin green aqueous solution on adsorption rate

[0045]

[0046] It can be seen from Table 2 that when the initial concentration of alizarin green is 40 μg / mL, the adsorption rate reaches the maximum. When the initial concentration of alizarin green is low, the capture efficiency of the adsorbent decreases, so the adsorption rate is low. When the initial concentration of alizarin green is too high, the adsorbent reaches functional saturation and cannot adsorb more alizarin green, so the adsorption rate decreases accordingly.

[0047] Example 6: Taking the adsorption temperature as a variable, the effect of the optimized temperature on the adsorption effect was screened as follows:

[0048] The rest is the same as Example 1, except that the adsorption temperature is set to 25, 30, 35, 40, and 45° C.; adsorption treatment is performed respectively, and the results are shown in Table 1:

[0049] Table 3 Effect of adsorption temperature on adsorption rate

[0050]

[0051]

[0052] It can be seen from Table 3 that with the increase of temperature, the adsorption rate of the adsorbent gradually decreases.

[0053] Example 7: Taking the adsorption time as a variable, the oscillation adsorption treatment time was screened and optimized as follows:

[0054] The rest is the same as Example 1, except that the adsorption time is set to 20, 40, 60, 80, 100, 120, and 180 min respectively; the adsorption treatment is performed respectively, and the results are shown in Table 1:

[0055] Table 4 Effect of adsorption time on adsorption rate

[0056]

[0057] It can be seen from Table 4 that when the adsorption time does not exceed 120 min, the adsorption rate gradually increases with the extension of the adsorption time. However, when the adsorption time exceeds 120 min, the adsorption efficiency decreases significantly. The main reason is that the adsorbed alizarin green is desorbed back into the aqueous solution. Therefore, the adsorption time is selected as 120 min.

[0058] Example 8: Taking the pH value of the alizarin green aqueous solution as a variable, the effect of pH on the adsorption effect was investigated as follows:

[0059] The rest is the same as Example 1, except that the pH is set to 1, 2, 4, 6, 8, 10, and 11 respectively; adsorption treatment is performed respectively, and the results are shown in Table 1:

[0060] Table 5 Effect of the acidity and alkalinity of aqueous solution on adsorption rate

[0061]

[0062] As can be seen from Table 5, the adsorption characteristics of chitosan-modified ferroferric oxide on alizarin green are that better adsorption effect can be achieved under strong acid conditions, and the adsorption efficiency is higher.

[0063] Comparative Example 1: The rest is the same as Example 1, except that:

[0064] Replace Alizarin Green with Alizarin Red.

[0065] Comparative Example 2: The rest is the same as Example 1, except that:

[0066] Replace Alizarin Green with Alizarin Blue.

[0067] Comparative Example 3: The rest is the same as Example 1, except that:

[0068] Replace Alizarin Green with Acid Alizarin Black.

[0069] Comparative Example 4: The rest is the same as Example 1, except that:

[0070] Chitosan is used to replace chitosan-modified ferrosoferric oxide.

[0071] Comparative Example 5: The rest is the same as Example 1, except that:

[0072] The ferroferric oxide powder is used to replace the chitosan-modified ferroferric oxide.

[0073] Comparative Example 6: The rest is the same as Example 1, except that:

[0074] Dextran was used to replace chitosan to prepare the adsorbent.

[0075] Comparative Example 7: The rest is the same as Example 1, except that:

[0076] Sodium carboxymethyl cellulose was used to replace chitosan to prepare the adsorbent.

[0077] The adsorption rates of Examples 1-3 and Comparative Examples 1-7 were measured, and the results were as follows:

[0078] Table 6 Adsorption effect of adsorbent samples on anthraquinone dyes

[0079] Group Adsorption rate (%) Example 1 55.6 Example 2 54.1 Example 3 55.2 Comparative Example 1 22.8 Comparative Example 2 8.4 Comparative Example 3 10.7 Comparative Example 4 21.3 Comparative Example 5 0.2 Comparative Example 6 25.6 Comparative Example 7 15.4

[0080] The results in Table 6 show that the chitosan-modified ferroferric oxide in Comparative Examples 1-3 has poor adsorption effects on other types of anthraquinone dyes, and only has excellent adsorption effects on alizarin green. Comparative Examples 4 and 5 show that the effect of chitosan alone for adsorption is also poor, and ferroferric oxide powder has almost no adsorption function for alizarin green, and only after chitosan modification of ferroferric oxide has excellent specific adsorption function for alizarin green. Comparative Examples 6 and 7 show that other types of polysaccharides modified ferroferric oxide cannot significantly improve the adsorption effect of the adsorbent on alizarin green.

Claims

1. A method for preparing chitosan-modified ferrosoferric oxide, characterized in that: The steps include: (1) mixing an alcohol solvent and ferric chloride, adding chitosan, and stirring to obtain a first reaction solution; (2) adding an alcohol solution of sodium acetate to the first reaction solution, stirring vigorously and then heating to react to obtain a first product; (3) Cooling the first product and separating it with a magnet to obtain a black substance, washing and drying the black substance to obtain chitosan-modified ferrosoferric oxide.

2. The method for preparing chitosan-modified ferrosoferric oxide according to claim 1, characterized in that: In step (1), the alcohol solvent includes at least one of ethylene glycol, propylene glycol, butylene glycol and pentanediol, and the ferric chloride is FeCl3·6H2O.

3. The method for preparing chitosan-modified ferrosoferric oxide according to claim 1, characterized in that: In step (1), the solid-liquid ratio of chitosan, ferric chloride and alcohol solvent is 0.5-1.5 g: 2-5 g: 60-100 mL.

4. The method for preparing chitosan-modified ferrosoferric oxide according to claim 1, characterized in that: In step (2), the alcohol solution of sodium acetate is prepared by dissolving 10-14 g of sodium acetate in 15-25 mL of ethylene glycol, and the volume ratio of the alcohol solution of sodium acetate to the alcohol solvent is 1:3-5.

5. The method for preparing chitosan-modified ferrosoferric oxide according to claim 1, characterized in that: In step (2), the vigorous stirring time is at least 20 minutes, and the heating reaction conditions are 170-200° C. and the reaction time is 10-14 hours.

6. The method for preparing chitosan-modified ferrosoferric oxide according to claim 1, characterized in that: In step (3), the washing method is to use ultrapure water and anhydrous ethanol for washing.

7. Use of chitosan-modified ferrosoferric oxide prepared according to the preparation method according to any one of claims 1 to 6 in adsorbing alizarin green in water.

8. The use according to claim 7, characterized in that: The method comprises the steps of mixing chitosan-modified ferroferric oxide with an alizarin green aqueous solution, performing oscillation adsorption, and magnetically separating the chitosan-modified ferroferric oxide after adsorption.

9. The use according to claim 8, characterized in that: The concentration of the alizarin green aqueous solution is 10-80 μg / mL, and the pH value is 2-11; the material-liquid ratio of the chitosan-modified ferroferric oxide to the alizarin green aqueous solution is 10-30 mg: 1-30 mL.

10. The use according to claim 8, characterized in that: The conditions of the oscillating adsorption are mechanical oscillating adsorption at 25-45° C. for 20-180 min.